2023
DOI: 10.1111/jopr.13743
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological profile of peri‐implantitis: Analyses of peri‐implant microbiome

Anmar Kensara,
Hanae Saito,
Emmanuel F. Mongodin
et al.

Abstract: PurposeTo characterize the microbiome composition in peri‐implant pocket of peri‐implantitis and peri‐implant sulcus controls using 16S rRNA gene sequencing.Materials and MethodsIn this controlled clinical cross‐sectional study, 23 subjects with control implants (n = 14) and diseased implants (peri‐implantitis, n = 21) were included. The peri‐implant pocket/sulcus was sampled and used to extract DNA and amplify the 16S rRNA gene using universal primers targeting the V3‐V4 regions. The resulting 16S PCR amplico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Recent studies based on the transcriptomic analysis of peri-implantitis and periodontitis sites from the same subject claim that the microbial compositions of both groups differed, with the microbiota of peri-implantitis being more complex than that of periodontal disease [15,16]. In addition, another study using the same analysis showed that plasmin receptor/glyceraldehyde-3-phosphate dehydrogenase gene activity was higher in peri-implant disease, suggesting significant changes in the pathogenic activity of the disease and the complexity of its microbiota [11].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies based on the transcriptomic analysis of peri-implantitis and periodontitis sites from the same subject claim that the microbial compositions of both groups differed, with the microbiota of peri-implantitis being more complex than that of periodontal disease [15,16]. In addition, another study using the same analysis showed that plasmin receptor/glyceraldehyde-3-phosphate dehydrogenase gene activity was higher in peri-implant disease, suggesting significant changes in the pathogenic activity of the disease and the complexity of its microbiota [11].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have used culture-based methods, DNA-DNA hybridisation techniques, or 16S rRNA gene amplicon sequencing to increase knowledge about the pathogens associated with PIM infections [10][11][12][13]. Research using real-time PCR has associated the typical periodontopathogens Porphyromonas gingivalis and Fusobacterium nucleatum with PD but not with PI [14].…”
Section: Introductionmentioning
confidence: 99%